1979
DOI: 10.1029/ja084ia06p02619
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of terrestrial kilometric radiation at very high altitudes

Abstract: On a number of occasions during the 3.5‐yr operating lifetime of Rae 2, we observed strong terrestrial kilometric radiation when the spacecraft was over the far side of the moon and when the low‐altitude terrestrial magnetosphere was completely obscured from view. If these deep lunar occultation events are used to infer radio source locations, then we find that the apparent source must sometimes be situated at geocentric distances of 10–40 RE or more. From an analysis of these events, we show that they are pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…A number of investigations have placed the location of this source region along auroral field lines at geocentric distances between about 1.5 and 3.5 R e [Gurnett, 1974;Kurth et ., 1975;Green et al, 1977;Alexander et al, 1979;Benson and Calvert, 1979;Gallagher and Gurnett, 1979;Morioka et al, 1981;Calvert, 1981b]. All of the AKR observations interpreted as x-mode were either made from polar orbiting satellites or from spacecraft very distant from the earth so that radiation from the polar regions could be directly received.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigations have placed the location of this source region along auroral field lines at geocentric distances between about 1.5 and 3.5 R e [Gurnett, 1974;Kurth et ., 1975;Green et al, 1977;Alexander et al, 1979;Benson and Calvert, 1979;Gallagher and Gurnett, 1979;Morioka et al, 1981;Calvert, 1981b]. All of the AKR observations interpreted as x-mode were either made from polar orbiting satellites or from spacecraft very distant from the earth so that radiation from the polar regions could be directly received.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the emission extended over a wider range of Earth distances from 2 to 20 Re, including the dayside cusp region. However, these surprisingly large distances were later reinterpreted as likely due to scattering, probably by density inhomogeneities in the magnetosheath [ Alexander et al , 1979].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few experiments on HF wave scattering from high altitude irregularities have been done [Gurevich et al, 1992], with somewhat controversial results [Greenwald, 1994;Guterich et al, 1994] or with indications that greater detection sensitivity is needed [Hysell et al, 1997]. Previous measurements of wave scattering in space plasmas [Alexander et al, 1979] have suggested the use of spacecraft receivers be-…”
Section: Introductionmentioning
confidence: 99%